THE DIFFICULTIES FACED AND REASONS EXPRESSED BY YAPEN WAROPEN'S STUDENTS OF ENGLISH IN PRONOUNCING SOME ENGLISH PHONEMES WHICH ARE NOT FOUND IN AMBAI LANGUAGE - Wanggai, Phillips Leuwnard (2012)
Ambai Language is spoken by people of Yapen Waropen regency in Papua. The implementation of teaching English in Yapen Waropen regency still reflect many problems. One of the challenges comes from the fact that some of English consonants and vowels sound are not found in Ambai Language. Thus, the Yapen Waropen's Students of English may have problems in pronouncing these speech sounds. This study attempts to find the answer to the following questions : (1) What difficulties are faced by the Yapen Waropen's students of English in pronouncing some English phonemes which are not found in Ambai Language ? (2) What are possible reasons of difficulties ? However, the problems above are so broad, and need to be limited. Thus the analysis focuses on the difficulties faced and reasons expressed by the Yapen Waropen's students of English in pronouncing these English speech sounds : [@3;], [ð], [θ], [l], [A8;], [C6;], [ɚ],[?3;],[¨»],[;4;],[ə],[;6;], and [?1;]. This study has used purposive sampling involving 12 elementary schools students and junior secondary high schools students. The writer chose several words in which the target English phonemes can be identified in front, central, and final position. To find students difficulties in pronouncing the Target English Speech Sounds, the subject were asked to pronounce those speech sounds of selected words. Ambai Language has 52 phonemes consist of 22 consonants, 12 vowels, and 18 diphthongs. Having phonemes above, the writer introduces the Difficulties Faced and Reasons Expressed by the Yapen Waropen's students of English in pronouncing some English phonemes which occurring in Front Central and Final position of selected words. The results show that the Yapen Waropen's students of English find it difficult to pronounce the phonemes above in front, central, and final position. This is because of there reasons : (1) Ambai Language doesn't have phoneme stated above, (2) There is an influence of Ambai Language phonemes when students pronouncing English phonemes, (3) Yapen Waropen's students of English are still in the process of acquiring English.